Catholic Religious Learning with the Project Based Learning (PjBL) Approach: Validity and Feasibility - Mite, Agustina Dede; Eveline, Siregar; Robinson, Situmorang (Journal of Education Reseach and Evaluation, 2021)
Teachers as one of the most important components in learning are required to be able to design appropriate learning activities and they can create a pleasant learning atmosphere for students, so that students can actively participate in the learning process. This study aims to develop Catholic Religion learning approach on project-based learning which isthat can help teacher and students in the learning process as one of a learning strategy to overcome the problem facing by teachers who only focus on the result of cognitive aspect. The procedure in developing Catholic Religion subject uses Instructional Development Model (IDM) with project-based learning on instructional design steps. Data collection is conducting by observation, interview, and questionnaire. Data analysis is mix-method. The results according to material expert review is 95,4% with very good qualification and it can be used without any revision and according to design instructional expert review is 91,2% with very good qualification and it can be used without revision too as well. Learning development by using project-based learning approach will be very effective to achieve learning objectives optimally both in cognitive and effective aspects. The implication of this research implies that learning development by project-based learning is very useful in learning Catholic Religion especially in affective aspect. So the learning objective either cognitive and affective aspects can be achieved.